INVESTASI LANGSUNG LUAR NEGERIDAN PERTUMBUHAN EKONOMI - Hindrayani, Aniek (ED EQUILIBRIUM, 2013)
Foreign Direct Investment flows have become a major part of capital flows inthe world economy. Through FDI, the economy has been transformed fromagricultural and exploitation of raw materials into producers and exporters ofmanufactured goods. There are several factors affecting economic growth of a country. In Indonesia, FDI is one of the factors that had positive relationship with economic growth.Inefficient beaureaucracy and bad infrastructure are still the major problem affecting FDI inflows in Indonesia. Government has develops strategy to raise the FDI inflows which were create rules and regulations and infrastructure buildup.